Subregional differences in intrinsic amygdala hyperconnectivity and hypoconnectivity in autism spectrum disorder. Issue 7 (15th December 2015) - Kleinhans, Natalia M.; Reiter, Maya A.; Neuhaus, Emily; Pauley, Greg; Martin, Nathalie; Dager, Stephen; Estes, Annette
Abstract : The amygdala is a complex structure with distinct subregions and dissociable functional networks. The laterobasal subregion of the amygdala is hypothesized to mediate the presentation and severity of autism symptoms, although very little data are available regarding amygdala dysfunction at the subregional level. In this study, we investigated the relationship between abnormal amygdalar intrinsic connectivity, autism symptom severity, and anxiety and depressive symptoms. We collected resting state fMRI data on 31 high functioning adolescents and adults with autism spectrum disorder and 38 typically developing (TD) controls aged 14–45. Twenty‐five participants with ASD and 28 TD participants were included in the final analyses. ASD participants were administered the Autism Diagnostic Interview–Revised and the Autism Diagnostic Observation Schedule. Adult participants were administered the Beck Depression Inventory II and the Beck Anxiety Inventory. Functional connectivity analyses were conducted from three amygdalar subregions: centromedial (CM), laterobasal (LB) and superficial (SF). In addition, correlations with the behavioral measures were tested in the adult participants. In general, the ASD group showed significantly decreased connectivity from the LB subregion and increased connectivity from the CM and SF subregions compared to the TD group. We found evidence that social symptoms are primarily associated with under‐connectivity from the LB subregion whereas over‐connectivity and under‐connectivity from the CM, SF and LB subregions are related to co‐morbid depression and anxiety in ASD, in brain regions that were distinct from those associated with social dysfunction, and in different patterns than were observed in mildly symptomatic TD participants. Our findings provide new evidence for functional subregional differences in amygdala pathophysiology in ASD. Autism Res 2016, 9: 760–772 . © 2015 International Society for Autism Research, Wiley Periodicals, Inc.